2014
DOI: 10.5009/gnl.2014.8.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response and the Tumor Microenvironment: How They Communicate to Regulate Gastric Cancer

Abstract: Gastric cancer is the second most common cause of cancer-related death in the world. A growing body of evidence indicates that inflammation is closely associated with the initiation, progression, and metastasis of many tumors, including those of gastric cancer. In addition, approximately 60% of the world's population is colonized by Helicobacter pylori, which accounts for more than 50% of gastric cancers. While the role of inflammation in intestinal and colonic cancers is relatively well defined, its role in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
115
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(122 citation statements)
references
References 74 publications
5
115
0
2
Order By: Relevance
“…Recent findings have shown that even in the absence of H. pylori infection, chronic inflammation can promote gastric oncogenesis [1]. Multiple genetic and epigenetic alterations in GC patients have been strongly associated with host immune responses [12]. Appropriate host T cell immunity is critical in response to and clearance of Helicobacter infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings have shown that even in the absence of H. pylori infection, chronic inflammation can promote gastric oncogenesis [1]. Multiple genetic and epigenetic alterations in GC patients have been strongly associated with host immune responses [12]. Appropriate host T cell immunity is critical in response to and clearance of Helicobacter infection.…”
Section: Discussionmentioning
confidence: 99%
“…Both exogenous stimuli, such as infection with microbes, and endogenous factors result in TSLP production. Previous studies demonstrated that H. pylori infection directly induced TSLP production from human gastric epithelial cells [12,24]. Recent research showed that TSLP could be involved in the progression of breast, lung, pancreatic, and cervical cancers; however, the regulatory mechanisms of TSLP in these cancers are not well defined [25][26][27][28].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the heterogeneous prognosis among gastric cancer patients necessitated the seek of effective biomarkers for the early detection and outcome prediction. Recently, chronic inflammation was found to plays a critical role in the initiation and progression of numerous cancers, including gastric cancer [15,16]. Interestingly, cancer cells can recruit and activate various leukocytes (especially neutrophils and monocytes) by T cells, specific chemokines and prostaglandins [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has been considered that the occurrence of GC is closely related to Helicobacter pylori infection, gene mutation, diet, and other risk factors. [3][4][5] Despite much progress in the treatment of GC, the overall 5 year survival rate of patients with GC is still less than 30%. 6 Heterogeneity and a lack of effective therapeutic targets are the two major obstacles to the precise treatment of GC.…”
mentioning
confidence: 99%